2019
DOI: 10.1136/bjophthalmol-2019-314567
|View full text |Cite
|
Sign up to set email alerts
|

Foveal avascular zone morphology and parafoveal capillary perfusion in sickle cell retinopathy

Abstract: Background/aimsTo assess foveal avascular zone (FAZ) morphology and parafoveal capillary perfusion in patients with various stages of sickle cell retinopathy (SCR) using optical coherence tomography angiography (OCT-A).MethodsThis is a multi-institutional retrospective study of patients with various stages of SCR compared with healthy controls. Parafoveal OCT-A images obtained using a commercial spectral domain-OCT system were reviewed. Foveal-centred 3×3 mm full vascular slab OCT-As were used for image proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 34 publications
1
7
1
Order By: Relevance
“…This suggests that the mechanisms involved in the peripheral SCDR and in the macular alterations are different. Moreover, we did not find any association between macular vascular density and peripheral non perfusion unlike in vein occlusions 29 , confirming previous results 30 . We can assume that no difference between genotypes is observed, since the DCP, mainly involved in SCD maculopathy, is composed only by vein 31 .…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that the mechanisms involved in the peripheral SCDR and in the macular alterations are different. Moreover, we did not find any association between macular vascular density and peripheral non perfusion unlike in vein occlusions 29 , confirming previous results 30 . We can assume that no difference between genotypes is observed, since the DCP, mainly involved in SCD maculopathy, is composed only by vein 31 .…”
Section: Discussionsupporting
confidence: 92%
“…1). Similarly, Lynch et al [23]reported foveal avascular zone and parafoveal capillary density abnormalities in eyes with sickle cell retinopathy compared to controls. As reported by others, the structural OCT abnormalities in the patients in this series were most evident in the temporal quadrant.…”
Section: Discussionmentioning
confidence: 93%
“…16 Currently, it is measured to quantify the disruption of the terminal capillary ring at the fovea; it has been shown to be associated with disease progression in vascular maculopathy. 11,12,17 Reduced FAZ circularity in the amblyopic eyes indicates a more irregular FAZ shape in comparison with that of the fellow eyes, showing unequal interocular development of the macular vascular network. Our results are consistent with a population-based nested case-control study of 30 children with amblyopia and 1,045 controls conducted by Wong and colleagues, 18 who reported a reduced FAZ circularity (measured by OCTA) in strabismic and anisometropic amblyopic eyes relative to control eyes.…”
Section: Discussionmentioning
confidence: 98%